Impact of steel-concrete slippage on CFST column load capacity under complex loading conditions - Pham My; Dinh Ngoc Hieu; Le Khanh Toan; Dang Cong Thuat (Tạp chí Khoa học và Công nghệ)
Concrete-Filled Steel Tubular (CFST) columns are composite structures consisting of a steel tube and a concrete core, offering high load-bearing capacity, especially under complex loading conditions. When CFST columns are subjected to simultaneous compression, bending and torsion, the interaction between the concrete core and the steel tube plays a crucial role in the distribution of stress and deformation. A key factor that needs to be assessed is the relative slippage between the steel tube and the concrete core, as it directly impacts the load-bearing capacity and stability of the column. This study shows that when compression/bending and torsion are applied simultaneously, the bond between the concrete core and steel tube may weaken, leading to slippage, which in turn reduces the structural system’s load-bearing efficiency. Understanding and accurately assessing the impact of this slippage is essential for improving design, ensuring CFST columns achieve optimal load-bearing performance in practice.